THE EFFECT OF IMPLEMENTING MERDEKA BELAJAR CURRICULUM AND LEARNING ENVIRONMENT ON LEARNING ACHIEVEMENT MEDIATED BY LAERNING INTEREST - Riastuti, Ayu; Nurjanah, Siti; Pratama, Aditya (International Journal of Multidisciplinary Research and Literature, 2024)
This study was conducted to determine how much influence the application of an merdeka belajar curriculum, learning environment and learning interest has on the learning achievement of economics class XI students of SMA Negeri 18 Jakarta with learning interest as an intervening variable. The method used is a quantitative method with a causal approach. The population in this study were grade XI students of SMA Negeri 18 Jakarta, totaling 119 students. Determination of the sample using random sampling technique and get a sample of 92 students. The data collection technique in this study is primary data for variable (X) and secondary data for variable (Y). the results of this study indicate that there is a positive and significant relationship directly or indirectly between the independent variable and the dependent variable